Optimizing Puzzle Media to Reduce Hyperactive Behavior in Early Childhood - Aida Haryanti; Sri Slamet (Universitas Muhammadiyah Surakarta, 2025)
Hyperactive behavior in Early childhood such as difficulty focusing, impulsivity, and spontaneous aggressiveness, is a problem that needs to be addressed early interactive learning media, such as puzzle are believed to improve children's concentration self- control and social skills. This study aims to determine the effect of optimizing puzzle media to reduce hyperactive behavior in early childhood. The research approach uses a descriptive qualitative method with one subject with the initials D, who exhibits hyperactive behavior in BA Aisyiyah VII Grogol. Data were collected through observation, interviews with teacher and parents documentation of photos and children's work and a questionnaire on the frequency of hyperactive behavior. Data analysis follows the Miles and Huberman Model (1994) through data reduction, presentation, and verification through triangulation. The result of the study show that providing puzzles regularly twice per week for three months improves children's focus reduces impulsive behavior spontaneous aggressiveness, improves the ability to complete task, and improves social skills and cooperation. Teachers and parents also reported. Prove positive changes in children's self control. Thus optimizing puzzle media is to be proven effective as a learning strategy to reduce hyperactive behavior while improving self-regulation and social skills in early childhood improving self regulation and social skills is early childhood.